Elliptic flow of identified hadrons in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Journal of high energy physics, 2015)
The elliptic flow coefficient (v 2) of identified particles in Pb-Pb collisions at sNN−−−√=2.76 TeV was measured with the ALICE detector at the Large Hadron Collider (LHC). The results were obtained with the Scalar Product method, a two-particle correlation technique, using a pseudo-rapidity gap of |Δη| > 0.9 between the identified hadron under study and the reference particles. The v 2 is reported for π ±, K±, K 0S , p+p¯¯¯, ϕ, Λ+Λ¯¯¯¯, Ξ−+Ξ¯¯¯¯+ and Ω−+Ω¯¯¯¯+ in several collision centralities. In the low transverse momentum (p T) region, p T < 3 GeV/c, v 2(p T) exhibits a particle mass dependence consistent with elliptic flow accompanied by the transverse radial expansion of the system with a common velocity field. The experimental data for π ± and the combined K± and K 0S results, are described fairly well by hydrodynamic calculations coupled to a hadronic cascade model (VISHNU) for central collisions. However, the same calculations fail to reproduce the v 2(p T) for p+p¯¯¯, ϕ, Λ+Λ¯¯¯¯ and Ξ−+Ξ¯¯¯¯+. For transverse momentum values larger than about 3 GeV/c, particles tend to group according to their type, i.e. mesons and baryons. The present measurements exhibit deviations from the number of constituent quark (NCQ) scaling at the level of ±20% for p T > 3 GeV/c.